2010
DOI: 10.3858/emm.2010.42.9.062
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuretin protects against cytokine-induced β-cell damage and prevents streptozotocin-induced diabetes

Abstract: NF-κB activation has been implicated as a key signaling mechanism for pancreatic β-cell damage. Sulfuretin is one of the main flavonoids produced by Rhus verniciflua, which is reported to inhibit the inflammatory response by suppressing the NF-κB pathway. Therefore, we isolated sulfuretin from Rhus verniciflua and evaluated if sulfuretin could inhibit cytokine-or streptozotocin-induced β-cell damage. Rat insulinoma RINm5F cells and isolated rat islets were treated with IL-1β and IFN-γ to induce cytotoxicity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 57 publications
(61 reference statements)
2
35
0
1
Order By: Relevance
“…inhibit cytokine-or streptozotocin-induced damage in rat insulinoma β-cells and in isolated cells that induced toxicity (Song et al, 2010).…”
Section: B Natural Plant Biomolecules With Antidiabetic Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…inhibit cytokine-or streptozotocin-induced damage in rat insulinoma β-cells and in isolated cells that induced toxicity (Song et al, 2010).…”
Section: B Natural Plant Biomolecules With Antidiabetic Actionmentioning
confidence: 99%
“…It is normally held in its inactive form by being bound to the inhibitory IκB molecule. However, it may be activated if IκB undergoes phosphorylation by I-Kappa-B kinase (IKK), leading to the release and activation of NF-κB that may induce pancreatic β-cell damage (Song et al, 2010;Stumvoll et al, 2005). The activation of the nuclear factor NF-κB by stress factors (cytokine molecules and free radicals) is strongly connected to β-cell damage.…”
Section: B Natural Plant Biomolecules With Antidiabetic Actionmentioning
confidence: 99%
“…Sulfuretin has anti-platelet, anti-mutagenic, and anti-infl ammatory effects. Recent studies have demonstrated that sulfuretin blocks the infl ammatory response in type 1 diabetes and allergic airway infl ammation models by suppressing the nuclear factor-B pathway ( 35,36 ). Fisetin is common in various vegetables and fruits, including RVS.…”
Section: The Tgf-␤ Pathway Mediates the Anti-adipogenic Effects Of Bumentioning
confidence: 99%
“…In another study, a homoisofl avoneenriched fraction with an insulin sensitizing effect was initially extracted from L. platyphylla with 70% ethanol and sequentially separated with Diaion HP-20 and silica gel column chromatography (Choi et al, 2004). Sulfuretin, one of the main fl avonoids of Rhus vernicilua, can completely prevent the hyperglycemia and hypoinsulinemia induced by streptozotocin (Song et al, 2010). Especially, some aqueous extracts display anti-diabetic activity.…”
Section: Discussionmentioning
confidence: 99%